Quantification of acromioclavicular reduction parameters after the Weaver-Dunn procedure - KÜÇÜKDURMAZ, FATİH; EKİNCİ, GAZANFER; BEZER, MURAT (SPRINGER, 2009)
The combination of the reconstruction of the coracoclavicular ligaments with the resection arthroplasty of the distal end of the clavicle is a commonly used technique in acromioclavicular separations. The purpose of the current study was to quantify the reduction parameters using 3-D CT and to analyze their effects on clinical outcomes. Case series. The patients with chronic symptoms after acromioclavicular dislocation (type III) were treated with reconstruction of the coracoclavicular ligaments. The average follow-up was 69.5 months. The patient group consisted of 21 men and 8 women. The initial treatment at the time of injury was nonoperative in 26 of 29 patients. CT was used to document anteroposterior (APD), craniocaudal (CCD) and mediolateral (MLD) acromioclavicular reduction parameters. Constant Shoulder scoring system was used. The mean preoperative Constant score was 56.62 +/- A 18.63 points while the postoperative score was 89.93 +/- A 10.79 points. The mean APD was 9.2 mm, the mean CCD was 1.1 mm and the mean MLD was 8.4 mm. There was no correlation between the APD, MLD and the Constant Scores. However, an inverse correlation between the CCD and the postoperative Constant Scores was found. CCD plays an important role on the postoperative function. If the CCD is larger, the Constant score is lower. The reduction loss is a distinctive parameter of the functional outcome, even when the reconstructed coracoclavicular ligament is intact. Secure fixation may be achieved with techniques preserving CCD.
Keywords: Acromioclavicular dislocation; Weaver-Dunn; Surgery; Shoulder; CT; CORACOCLAVICULAR LIGAMENT RECONSTRUCTION; JOINT INJURIES; SURGICAL-TREATMENT; SEPARATION; DISLOCATIONS